Analysis of sleep problem in children aged 1–3 years with autism spectrum disorder in Zhejiang province, China - Yao, Dan; Wang, Shasha; Li, Fangfang; Gao, Minjie; Shao, Jie (Frontiers in Psychiatry, 2022)
Background High prevalence of sleep problems have been founded in children with Autism Spectrum Disorder(ASD)，with rates ranging from 50% to 80%. We aimed to study the sleep status and the occurrence of sleep problems in children with autism spectrum disorder （ASD） aged 1-3 years, and to provide reference for guiding early comprehensive intervention for ASD children from the perspective of sleep. Methods From January 1 to December 31，2021, 74 ASD children who met the diagnostic criteria of "Diagnostic and Statistical Manual of Mental Disorders-5（DSM-V）" served as case group while 84 typically-developing children of the same sex and age served as control group. An original Children's Sleep Habit Questionnaire was adopted to compare the sleep status of children in the two groups and to conduct statistical analysis on related factors. Results The incidence of sleep problems in the case group (78.4%) was significantly higher than that in the control group (34.5%)（P＜0.001）. Compared with the children in the control group, children in the case group had later bedtime （P＜0.05）and less sleep duration（P＜0.05）, and required longer time to fall asleep （P＜0.001） The incidence of sleep problems in children who could fall asleep autonomously in the case group was significantly lower than that in children who needed parental help（P＜0.05）. In the case group, the longer the screen exposure time, the higher the incidence of sleep problems（P＜0.05）. Conclusions The incidence of sleep problems in ASD children aged 1-3 years is also high, mainly manifested in late bedtime, difficulty falling asleep, frequent night awakenings and less sleep duration. Both sleep patterns and screen exposure can impact their sleep. In the early comprehensive intervention of ASD children, it is necessary to pay full heed to their sleep status and take timely intervention measures in order to improve the quality of life for the ASD children and their families.